Preparation of a live donor for nephrectomy for transplantation – case report - Hreńczuk, Marta; Małkowski, Piotr (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2020)
Nephrectomy is a procedure that has been performed in urology and abdominal surgery for over 100 years. This procedure is performed not only for therapeutic reasons, but also for particularly healthy people, when they are qualified as living donors for transplantation. The aim of the study was to present the process of preparing a live donor for surgery to collect a kidney for transplantation, with particular attention to nursing care. This process is very complicated and requires a lot of research and consultation, which is designed to optimally select a donor for the recipient and to reduce the risk of complications for a donor who undergoes major nephrectomy surgery voluntarily without benefit to their physical health.